Government Gardens, Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
The postcard shows a variety of trees including palms in the Government Gardens in Trindad.
Colour: Black and white; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Palms--Trinidad and Tobago; Plants--Trinidad and Tobago; 1903; Gardens--Trinidad and Tobago; Historic gardens--Trinidad and Tobago